Posicionamento do Brasil face aos países mais avançados em cloud computing - Cândido, Ana Clara (2015)
This study discusses some fundamental issues so that the development and diffusion of services based in cloud computing happen positively in several countries. For exposure of this subject is discusses public initiatives by the most advanced countries in terms of cloud computing application and the brazilin position in this context. Based on presented evidences here it appears that the essential elements for the development and diffusion of cloud computing in Brazil made important steps and show evidence of maturity, as the cybercrime legislation. However, other elements still require analysis and specifically adaptations for the cloud computing case, such as the Intellectual Property Rights. Despite showing broadband services still lacking, one cannot disregard the government effort to facilitate access for all society. In contrast, the large volume of the Brazilian IT market is an interest factor for companies seeking to invest in the country.